Education In Structural Perspectives And Conflict On Social Relations In Community - Saputro, Noto; Ningsih, Tutuk (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Education is a foundation that must be built as well as possible. To form and develop students, it is necessary to pay attention and synergize all aspects related to education such as parents, community, school government. It aims to solve problems together if there are problems and negative symptoms in students. The purpose of this paper is to examine education in a structural perspective and conflict about social relations in society. The methodology used in this paper is a library research method using a data collection model in the form of a literature review that is relevant to the focus of the discussion in this article. The results of the discussion show that Education in structure and conflict sees that every individual in the class has different opinions, interests, and desires that can lead to conflict. Conflict can have both positive and negative consequences. Conflict in the classroom is positive when there is healthy competition between students.